Presence of dogs and proximity to a wildlife reserve increase household level risk of tungiasis in Kwale, Kenya - Peter S Larson; Masanobu Ono; Mwatasa Changoma; Kensuke Goto; Satoshi Kaneko; Kazuhiko Moji; Noboru Minakawa (Tropical Medicine and Health, 2021)
Abstract Introduction Tungiasis is a ectopic skin disease caused by some species of fleas in the Tunga genus, most notably T. penetrans. The disease afflicts poor and marginalized communities in developing countries. Transmission of tungiasis comprises a complex web of factors including domesticated animals and wildlife. This research explores animal and environmental risk factors for tungiasis in an area adjacent to a wildlife reserve in Kwale, Kenya. Methods A two-stage complex sampling strategy was used. Households were selected from three areas in and around Kwale Town, Kenya, an area close to the Kenyan Coast. Households were listed as positive if at least one member had tungiasis. Each household was administered a questionnaire regarding tungiasis behaviors, domesticated animal assets, and wild animal species that frequent the peridomiciliary area. Associations of household tungiasis were tests with household and environmental variables using regression methods. Results The study included 319 households. Of these, 41 (12.85%) were found to have at least one person who had signs of tungiasis. There were 295 (92.48%) households that possessed at least one species of domesticated animal. It was reported that wildlife regularly come into the vicinity of the home 90.59% of households. Presence of dogs around the home (OR 3.85; 95% CI 1.84; 8.11) and proximity to the park were associated with increased risk for tungiasis infestation in humans in a multivariate regression model. Conclusions Human tungiasis is a complex disease associated with domesticated and wild animals. Canines in particular appear to be important determinants of household level risk.